Hadith #588 - Sahih Muslim - Umm Salamah (Sahih Muslim)
While I was lying with the Messenger of Allah (ﷺ) in a bed cover I menstruated, so I slipped away and I took up the clothes (which I wore) in menses. Upon this the Messenger of Allah (ﷺ) said: Have you menstruated? I said: Yes. He called me and I lay down
Grade: Sahih

Hadith #617 - Sahih Muslim - Umm Salamah (Sahih Muslim)
Umm Sulaim went to the Messenger of Allah (ﷺ) and said: Apostle of Allah, Allah is not ashamed of the truth. Is bathing necessary for a woman when she has a sexual dream? Upon this the Messenger of Allah (ﷺ) said: Yes, when she sees the liquid (vaginal secretion). Umm Salama said: Messenger of Allah, does a woman have sexual dream? He (the Holy Prophet) said: Let your hand be covered with dust, in what way does her child resemble her?
Grade: Sahih

Hadith #649 - Sahih Muslim - Umm Salamah (Sahih Muslim)
I said: Messenger of Allah, I am a woman who has closely plaited hair on my head; should I undo it for taking a bath, because of sexual intercourse? He (the Holy Prophet) said: No, it is enough for you to throw three handfuls of water on your head and then pour water over yourself, and you shall be purified.
Grade: Sahih

Hadith #2013 - Sahih Muslim - Umm Salamah (Sahih Muslim)
If any Muslim who suffers some calamity says, what Allah has commanded him,” We belong to Allah and to Him shall we return; O Allah, reward me for my affliction and give me something better than it in exchange for it,” Allah will give him something better than it in exchange. When Abu Salama died she said: What Muslim is better than Abu Salama whose family was the first to emigrate to the Messenger of Allah (ﷺ). I then said the words, and Allah gave me God’s Messenger (ﷺ) in exchange.
Grade: Sahih

Hadith #2016 - Sahih Muslim - Umm Salamah (Sahih Muslim)
Whenever you visit the sick or the dead, supplicate for good because angels say” Amen” to whatever you say. She added: When Abu Salama died, I went to the Messenger of Allah (ﷺ) and said: Messenger of Allah, Abu Salama has died. He told me to recite:” O Allah! forgive me and him (Abu Salama) and give me a better substitute than he.” So I said (this), and Allah gave me in exchange Muhammad, who is better for me than him (Abu Salama).
Grade: Sahih

Hadith #2017 - Sahih Muslim - Umm Salamah (Sahih Muslim)
The Messenger of Allah (may peace be upon came to Abu Salama (as he died). His eyes were fixedly open. He closed them, and then said: When the soul is taken away the sight follows it. Some of the people of his family wept and wailed. So he said: Do not supplicate for yourselves anything but good, for angels say” Amen” to what you say. He then said: O Allah, forgive Abu Salama, raise his degree among those who are rightly guided, grant him a successor in his descendants who remain. Forgive us
Grade: Sahih

Hadith #2021 - Sahih Muslim - Umm Salamah (Sahih Muslim)
When Abu Salama died I said: I am a stranger in a strange land; I shall weep for him in a manner that would be talked of. I made preparation for weeping for him when a woman from the upper side of the city came there who intended to help me (in weeping). She happened to come across the Messenger of Allah (ﷺ) and he said: Do you intend to bring the devil into a house from which Allah has twice driven him out? I (Umm Salama), therefore, refrained from weeping and I did not weep.
Grade: Sahih

Hadith #2204 - Sahih Muslim - Umm Salamah (Sahih Muslim)
I asked the Messenger of Allah (ﷺ) whether there is a reward for me if I spend on Abu Salama’s sons, and I am not going to abandon them in this state (of helplessness) for they are my sons. He (the Holy Prophet) said: Yes. For you is the reward for what you spend on them.
Grade: Sahih

Hadith #2407 - Sahih Muslim - Umm Salamah (Sahih Muslim)
Apostle of Allah, you took an oath that you would not come to us for a month, whereupon he said: The month may also consist of twenty-nine days.
Grade: Sahih

Hadith #2958 - Sahih Muslim - Umm Salamah (Sahih Muslim)
I made a complaint to Allah’s Messenger (ﷺ) of my ailment, whereupon be said: Circumambulate behind the people while riding. She said: So I circumambulated and Allah’s Messenger (ﷺ) was at that time praying towards the side of the House and he was reciting al-Tur and a Book Inscribed (i. e. Sura Iii. of the Qur’un).
Grade: Sahih

Hadith #3462 - Sahih Muslim - Umm Salamah (Sahih Muslim)
It was said to the Messenger of Allah (ﷺ): Is not the daughter of Hamza a suitable match for you? Or it was said: Why don’t you propose to marry the daughter of Hamza, the son of Abd al-Muttalib? Thereupon he said: Hamza is my brother by reason of fosterage.
Grade: Sahih

Hadith #3480 - Sahih Muslim - Umm Salamah (Sahih Muslim)
A young boy who is at the threshold of puberty comes to you. I, however, do not like that he should come to me, whereupon ‘A’isha (Allah be pleased with her) said: Don’t you see in Allah’s Messenger (ﷺ) a model for you? She also said: The wife of Abu Hudhaifa said: Messenger of Allah, Salim comes to me and now he is a (grown-up) person, and there is something that (rankles) in the mind of Abu Hudhaifa about him, whereupon Allah’s Messenger (ﷺ) said: Suckle him (so that he may becom
Grade: Sahih

Hadith #3502 - Sahih Muslim - Umm Salamah (Sahih Muslim)
If you desire that I spend a week with you, I shall have to spend a week with my (other) wives, and if spend a week with you, I shall have to spend a week with my (other) wives.
Grade: Sahih

Hadith #4343 - Sahih Muslim - Umm Salamah (Sahih Muslim)
You bring to me, for (judgment) your disputes, some of you perhaps being more eloquent in their plea than others, so I give judgment on their behalf according to what I hear from them. (Bear in mind, in my judgment) if I slice off anything for him from the right of his brother, he should not accept that, for I sliced off for him a portion from the Hell.
Grade: Sahih

Hadith #4666 - Sahih Muslim - Umm Salamah (Sahih Muslim)
In the near future there will be Amirs and you will like their good deeds and dislike their bad deeds. One who sees through their bad deeds (and tries to prevent their repetition by his band or through his speech), is absolved from blame, but one who hates their bad deeds (in the heart of his heart, being unable to prevent their recurrence by his hand or his tongue), is (also) fafe ( so far as God’s wrath is concerned). But one who approves of their bad deeds and imitates them is spiritually r
Grade: Sahih

Hadith #4980 - Sahih Muslim - Umm Salamah (Sahih Muslim)
When any one of you intending to sacrifice the animal enters in the month (of Dhu’l-Hijja) he should not get his hair or nails touched (cut). It was said to Sufyan that some of the (scholars) did not deem this hadith to be Maffu’. He said: But I deem it as Marfu’ (i. e. chain of narration traceable right up to the Holy Prophet).
Grade: Sahih

Hadith #4981 - Sahih Muslim - Umm Salamah (Sahih Muslim)
If anyone of you intends to offer sacrifice he should not get his hair cut or nails trimmed.
Grade: Sahih

Hadith #4982 - Sahih Muslim - Umm Salamah (Sahih Muslim)
If anyone has in his possession a sacrificial animal to offer as a sacrifice (on ‘Id al-Adha), he should not get his hair cut and nails trimmed after he has entered the first days of Dhu’l Hijja
Grade: Sahih

Hadith #5543 - Sahih Muslim - Umm Salamah (Sahih Muslim)
Abdullahb. Aba Umayya. if Allah grants you victory in Ta’if on the next day, I will show you the daughter of Ghailan for she has four folds (upon her body) on the front side of her stomach and eight folds on the back. Allah’s Messenger (ﷺ) heard this and he said: Such (people) should not visit you.
Grade: Sahih

Hadith #5822 - Sahih Muslim - Umm Salamah (Sahih Muslim)
” O people.” And she said to one who was combing: Leave my head; the rest of the hadith is the same.
Grade: Sahih

Hadith #7143 - Sahih Muslim - Umm Salamah (Sahih Muslim)
A group of rebels would kill you.
Grade: Sahih

Hadith #7145 - Sahih Muslim - Umm Salamah (Sahih Muslim)
A band of rebels would kill `Ammar.
Grade: Sahih